Source compositions and melting temperatures of the main granitic suites from the Moldanubian Batholith - Rene,M. (Journal of Geosciences, 2016)
The granitoids of the Moldanubian Batholith (Moldanubian Zone of the Bohemian Massif) are represented by three main suites: I- to I/S-type Weinsberg biotite granites-granodiorites, S-type Eisgarn two-mica granites and I/S-type Freistadt biotite granites-granodiorites. As shown by major-element data and zircon with monazite saturation thermometry, partial melting of metapelites likely produced most of the Eisgarn suite (Mrakotin/Cimer varieties) at c. 775-825 °C. Parental melts of the Weinsberg and Freistadt suites could have been generated by partial melting of a metagreywackes-metabasalts mixture at c. 740-940 °C.This study confirms that the CaO/Na2O ratio could be used for source assignment of S-type granite melts, whereas the CaO/(FeO + MgO + TiO2) ratio is more suitable for I/S-type granites. The observed systematic positive shift of Al2O3/TiO2 temperatures compared with zircon and monazite saturation temperatures in all granitoids of the Moldanubian Batholith (up to 118 °C) may be explained by accumulation of ilmenite in the S-type Eisgarn suite. In the I- and I/S-granite types of the Weinsberg and Freistadt suites the Al2O3/TiO2 ratio is controlled by the accumulation of ilmenite and/or titanite. Consequently, the Al2O3/TiO2 ratio may be used as a thermometer only with caution.
Keywords: granites; petrology; geochemistry; Moldanubian zone; Bohemian Massif